2020
DOI: 10.3390/su12177204
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Quality of Urban Wetland Parks: A Second-Order Factor Structure Equation Modeling

Abstract: Wetland in the urban or peri-urban areas has been recognized as an important component of urban ecosystems and provides ecological and environmental services. Wetland park emerged as a kind of restoration of natural wetlands in the context of increasing pressure on land and eco-environment caused by urban sprawl, which has played an essential role in providing recreational spaces/opportunities and improving social interactions. However, little research has been conducted on the theoretical formulation elaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Furthermore, their study also showed that although landscape composition and arrangement both have an impact on LST, landscape composition is more important than landscape layout; thus, one component indicator (e.g., impervious surface) together with no more than four landscape layout indicators can well lead to the prediction of LST [23][24][25][26][27]. ese research results can help landscape ecologists effectively use landscape indicators and promote landscape planners to make balanced use of land use types (LUTs) in urban planning [28][29][30][31][32][33]. Mainly, land surface characteristics are primarily represented by land cover and land use (LCLU).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, their study also showed that although landscape composition and arrangement both have an impact on LST, landscape composition is more important than landscape layout; thus, one component indicator (e.g., impervious surface) together with no more than four landscape layout indicators can well lead to the prediction of LST [23][24][25][26][27]. ese research results can help landscape ecologists effectively use landscape indicators and promote landscape planners to make balanced use of land use types (LUTs) in urban planning [28][29][30][31][32][33]. Mainly, land surface characteristics are primarily represented by land cover and land use (LCLU).…”
Section: Introductionmentioning
confidence: 84%
“…After the establishment of the indexes, the same index value can contain different types of surface factors. Although the fitting with the LST can point to a specific trend and indicate a particular connection [24][25][26][27][28][29][30], we do not know precisely what type of surface factors respond to the thermal environment [4][5][6][7] and how much they are affected [8][9][10]. rough regression statistics, more than 95% of confidence level indicates that vegetation has the greatest influence on the rate of change of environmental temperature, with a contribution coefficient of about 0.17, followed by dark soil with a contribution coefficient of 0.16, and water bodies and buildings with high reflectivity have the least contribution coefficient to the thermal environment.…”
Section: Advances In Meteorologymentioning
confidence: 99%
“…These are positively related and shows us the probability that a citizen has a high level of well-being measured as satisfaction in the set of municipal services and recommends the city as a place to live, attracting population to it, facing the problem of depopulation. from urban areas [ 48 69 ] and these affect the likelihood that citizens will stay and recommend the urban area, thus avoiding the dreaded depopulation [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the essential components in urban system, outdoor and semi-outdoor environments can provide open spaces for hosting various recreational, social and commercial activities [16]. On the other hand, the outdoor green spaces in urban areas are facilitating to adapt to the increased heat stress and evolving into an important contribution to the energy efficiency of the surrounding buildings [17,18].…”
Section: Introductionmentioning
confidence: 99%